The russian orientalist alexander adamov writes about basra from the conquest to the end of the first abbasid era through his book wilayat al-basrah in its past and present - Bandar Khazal, Lect. Dr. Sondos (Basra studies journal, 2025)
The city of Basra has a historical importance as Basra in Islamic history due to its strategic location as it is located in southern Iraq at the confluence of the Tigris and Euphrates rivers, which made it an important commercial center between the East and the West. Basra was conquered by the early Muslims in 14 AH / 635 AD and was one of the main military camps of the Islamic army in its conquests. Basra quickly became a center of science and literature, where many famous scholars and jurists appeared. Basra played a major role in the Islamic conquests in the East, as it was a starting point for armies that headed to conquer Persia and Transoxiana. Basra contained many public and private libraries, which made it an important scientific repository in the Islamic world.